Knockdown of deleterious miRNA in progenitor cell–derived small extracellular vesicles enhances tissue repair in myocardial infarction - Park, Hyun Ji; Hoffman, Jessica R.; Brown, Milton E.; Bheri, Sruti; Brazhkina, Olga; Son, Young Hoon; Davis, Michael E. (Science Advances, 2023)
Small extracellular vesicles (sEVs) play a critical role in cardiac cell therapy by delivering molecular cargo and mediating cellular signaling. Among sEV cargo molecule types, microRNA (miRNA) is particularly potent and highly heterogeneous. However, not all miRNAs in sEV are beneficial. Two previous studies using computational modeling identified miR-192-5p and miR-432-5p as potentially deleterious in cardiac function and repair. Here, we show that knocking down miR-192-5p and miR-432-5p in cardiac c-kit+ cell (CPC)–derived sEVs enhances the therapeutic capabilities of sEVs in vitro and in a rat in vivo model of cardiac ischemia reperfusion. miR-192-5p–and miR-432-5p–depleted CPC-sEVs enhance cardiac function by reducing fibrosis and necrotic inflammatory responses. miR-192-5p–depleted CPC-sEVs also enhance mesenchymal stromal cell–like cell mobilization. Knocking down deleterious miRNAs from sEV could be a promising therapeutic strategy for treatment of chronic myocardial infarction.
Keywords: Cardiac cell; Cardiac functions; Cargo molecules; Cell therapy; Cellular signalling; Computational modelling; Extracellular; Myocardial Infarction; Progenitor cell; Tissue repair; Animals; Anti-Arrhythmia Agents; Cardiotonic Agents; Extracellular Vesicles; Heart; MicroRNAs; Myocardial Infarction; Rats; Stem Cells